Design and evaluation of an oral multiparticulate system for dual delivery of amoxicillin and Lactobacillus acidophilus. (September 2016) - Govender, Mershen; Choonara, Yahya E; van Vuuren, Sandy; Kumar, Pradeep; du Toit, Lisa C; Pillay, Viness
Aim: A delayed-release dual delivery system for amoxicillin and the probiotic Lactobacillus acidophilus was developed and evaluated.Materials & methods: Statistical optimization of a cross-linked denatured ovalbumin protective matrix was first synthesized using a Box–Behnken experimental design prior to encapsulation with glyceryl monostereate. The encapsulated ovalbumin matrix was thereafter incorporated with amoxicillin in a gastro-resistant capsule. In vitro characterization and stability analysis of the ovalbumin and encapsulated components were also performedResults: Protection of L. acidophilus probiotic against the bactericidal effects of amoxicillin within the dual formulation was determined.Conclusion: The dual formulation in this study proved effective and provides insight into current microbiome research to identify, classify and use functional healthy bacteria to develop novel probiotic delivery technologies.